ROYAL MILITARY COLLEGE THE PORT DICKSON YEARS : 1952-1961 - Muhammad Shuhud Saaid (Royal Military College Old Putera Association, 2007)
The Royal Military College started as the Boys' Company in September 1952 and came under the administration of the Malay Regiment Training Centre at Port Dickson. It was redesignated the Boy's Wing when the then Federation Military College was formed on 17th December 1953.